Hodnocení výkonnosti podniku podle Modelu START PLUS - Řehůřek, Lukáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Diplomová práce je zaměřená na hodnocení výkonnosti podniku AK signal Brno a.s. První část se zabývá literární rešerší, ve které je charakterizovaná výkonnost podniku, její hodnocení tradičními i moderními metodami, řízení kvality a společenské odpovědnosti podniku a představený Model START PLUS. Ve druhé části jsou uvedené výsledky hodnocení výkonnosti podniku zpracované popsaným Modelem START PLUS a jeho nástroji. Ve třetí části jsou popsané získané výsledky a následně doporučené vlastní návrhy, které vedou ke zlepšení výkonnosti podniku AK signal Brno a.s.

The diploma thesis is focused on the performance evaluation of AK signal Brno a.s. The first part deals with a literature research, in which the performance of the company characterized its own evaluation by traditional and modern methods. Furthermore, this part carriers out the quality management and the corporation with social responsibility, as well as, the presentation of START PLUS model. The second part presents the results of the evaluation of the enterprise performance processed by describing START PLUS Model and its tools. The third part ilustrates the results obtained and in addition recomends its own proposals that lead the improvement of the performance of AK signal Brno a.s.
Company Performance Assessment According to Model START PLUS
Keywords: Výkonnost podniku; moderní metody; řízení kvality; společenská odpovědnost; EFQM; START PLUS.; Business performance; modern methods; quality management; social responsibility; EFQM; START PLUS.